Between the Emancipation and the National: Literary Contributions in Journal Žena: књижевни прилози у часопису Жена (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes journal Womаn [Žena], which was launched and edited by Milica Tomić. Contextualization of the editorial policy of the journal shows its emancipatory-enlightening tendency, with special analysis of the role and importance of literary contributions. The aim of this paper is to present the role and the place of literature in the emancipatory process, as well as to show that Womаn [Žena] was a role model for the corps of journals with similar orientations in the history of the press that appeal to women.
Keywords: Žena [Womаn] 1911–1921; Milica Tomić; women’s magazines; emancipation; literary contributions